Chinese experience with global G3 standard-setting - John Whalley; Weimin Zhou; Xiaopeng An (Center for Economic Studies and ifo Institute (CESifo), 2009)
China's growth strategy as set out in the 11th 5-year plan in 2005 called for upgrading of product quality, the development of an innovation society, and reduced reliance on foreign intellectual property with high license fees. Consistent with this policy, China has been involved in recent years with the development of a Chinese standard in third generation (3G) mobile phone technology, both in negotiating the standard and seeing it through to commercialization. This is the first case of a developing country both originating and successfully negotiating a telecommunications standard and this experience raises issues for China's future development strategy based on product and process upgrading in manufacturing. We argue that while precedent setting from an international negotiating point of view, the experience has thus far is unproven commercially. But the lessons learned will benefit future related efforts in follow-on technologies if similar Chinese efforts are made. This paper documents Chinese standard-setting efforts from proposal submission to ITU to the current large-scale trial network deployment in China and overseas trial networks deployment. We discuss the underlying objectives for this initiative, evaluate its effectiveness, and assess its broader implications for Chinese development policy.;
Keywords: O57; 330; Mobilkommunikation; Normung; Forschungs- und Technologiepolitik; Produktqualität; Entwicklungsstrategie; China